THE ROLE OF ORGANIC MATTER ON IMPROVEMENT OF THE PROPERTIES OF KUSAMBA BEACH SAND SOIL, DAWAN SUB-DISTRICT, KLUNGKUNG REGENCY, BALI FOR WATERMELON (Citrullus lanatus Tunb) CULTIVATION - Wiyanti Wiyanti; Ni Nengah Soniari; I Nyoman Dibia (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2019)
The study on The Role of Organic Matter on Improvement of The Properties of Kusamba Beach Sand Soil, Dawan Sub-District, Klungkung Regency, Bali For Watermelon (Citrullus lanatus Tunb) Cultivation was conducted in the green house of Agriculture Faculty, Udayana University, Bali. The aim of this study was to determine the role of organic matter in the soil properties of beach sand (Entisol type) to increase crop productivity of watermelon. The research used pot experiment with completely randomized design (CRD) method. The treatments used was organic fertilizer of waste cattle with base fertilizer (N, P, K). The dosage of organic fertilizer were: P0 (20% of the weight of soil); P1 (40%); P2 (60%), and P3 (80%). Each treatment was repeated three times, so in total were 12 pots treatment. Organic matter can decrease bulk density, soil permeability, and increase the total porosity of the soil. It was also able to increase total nitrogen, availability P in soil, dry weight of crop and the weight of the fruit at harvest. The highest bulk density was at P0 and the lowest was at P3 or decreased by 23.17%. The soil porosity increased by 7.98%, while the soil permeability decreased by 26.29%. The highest of total Nitrogen and P availability at treatment P3 which increased by 100% and 135.33% repectively when compared with P0. The dry weight of crop and weight of fruit at harvest increased of 48.81% and 97.70% when compared with treatment of P0.